2011
DOI: 10.1111/j.1440-1681.2011.05588.x
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic muscarinic and adenosine receptors are involved in 2 Hz-induced train-of-four fade caused by antinicotinic neuromuscular relaxants in the rat

Abstract: 1. Train-of-four fade (TOF(fade) ) is a clinically useful parameter to monitor the degree of block of neuromuscular transmission in curarized patients. Experimentally, TOF(fade) has been attributed to the blockade of facilitatory nicotinic receptors on motor nerve terminals. There is less information regarding the involvement of coexistent presynaptic receptors (e.g. muscarinic M(1) and M(2) , adenosine A(1) and A(2A) ) in the TOF(fade) produced by antinicotinic agents. 2. In the present study, we evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…For example, muscarinic and purinergic receptors interact at presynaptic neuronal sides. Of these receptors, muscarinic facilitatory M 1 and inhibitory M 2 receptors regulate the fine‐tuning actions of ACh release on neuronal firing, and these receptors are in turn regulated by purinergic receptors …”
Section: Introductionmentioning
confidence: 99%
“…For example, muscarinic and purinergic receptors interact at presynaptic neuronal sides. Of these receptors, muscarinic facilitatory M 1 and inhibitory M 2 receptors regulate the fine‐tuning actions of ACh release on neuronal firing, and these receptors are in turn regulated by purinergic receptors …”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that a higher activation of M 1 receptors on motor nerve by acetylcholine might be occurring in the cisatracurium-induced 100% Fade. It has already been demonstrated that A-value is influenced by presynaptic M 1 receptors activity when the motor nerve is stimulated at 50.00 Hz trains (Oliveira, Timóteo & Sá, 2002 cisatracurium-induced Fade would be the expected effect when the preparations were previously treated with ZM241385 (Oliveira et al, 2002;Pereira et al, 2012), it was supposed that the anticholinesterase activity of cisatracurium (Bornia et al, 2009;Bornia et al, 2011;Pereira et al, 2011) in the experimental condition causing 100% Fade reduced the expression of facilitatory effect induced by the blockade of A 2A receptors by producing a level of M 1 /M 2 activation by acetylcholine higher than that determined by the separate treatment of preparations with cisatracurium. Indeed, the previous treatment of preparations with ZM241385 caused a reduction in the A-value induced by cisatracurium which was not significantly (p > 0.05) different from that obtained after the administration of cisatracurium.…”
Section: Resultsmentioning
confidence: 98%
“…conditions of neuromuscular transmission, as different patterns of stimulation applied on motor nerve in the absence or in the presence of drugs, may modify the autoregulatory cholinergic (facilitatory-nicotinic receptors expressing α3β2 subunits, facilitatory-M 1 and inhibitory-M 2 subtypes of muscarinic receptors) and the modulatory (facilitatory-A 2A and inhibitory-A 1 adenosine receptors) mechanisms on the terminal (Bornia, Bando, Machinsky, Pereira, & Prado, 2009;Pereira, Bornia, Sá, & Prado, 2011). Therefore, the Fade caused by antinicotinic (hexamethonium) agent may be severe (~ 89%) when the concentration of such agent is causing 25% TOF fade (Pereira, Sá, & Prado, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Four antinicotinic agents, namely D-tubocurarine, hexamethonium, pancuronium and cisatracurium, were evaluated in the present study. The concentrations that consistently produced approximately 25% TOF fade were determined in at least four individual preparations 16 ; these concentrations were used to investigate the effects of the antinicotinic muscle relaxants on the fading of tetanic contractions. The antinicotinic drugs under investigation were tested either in the absence or presence of the M 1 , M 2 , A 1 and A 2A receptor antagonists pirenzepine (10 nmol/L), methoctramine (1 lmol/L), 1,3-dipropyl-8-cyclopentylxanthine (DPCPX; 2.5 nmol/L) and 4-(2-[7-amino-2-(2-furyl) [1,2,4]triazolo [2,3-a][1,3,5]triazin-5-ylamino]ethyl) phenol] (ZM 241385; 10 nmol/L), respectively.…”
Section: Methodsmentioning
confidence: 99%